The authors' reply - Stange, Daniel Eduard; Radlwimmer, Bernhard (Gut, 2011)
A study of 100 patients requiring open-heart surgery has been undertaken to ascertain whether prophylactic measures designed to minimise cerebral damage have influenced the incidence or severity of changes in cerebral electrical activity recorded at the onset of cardiopulmonary bypass. The incidence of change in cerebral electrical activity remains high but the severity of the disturbances has diminished as compared with a series investigated before prophylactic measures were introduced. Changes suggestive of cerebral depression were particularly notable in children under 10 years of age. The significance of these findings is discussed in the context of factors which might influence cerebral electrical activity at the onset of bypass.
Online zuerst veröffentlicht 29 December 2010
Gesehen am 20.10.2022